Nature's elegiac poetry (ahelbait) By the poet: Haider Al-Helee - Ahmed Obaid, Hassanien (Journal of College of Education, 2021)
The words of nature received the attention of researchers and scholars, and many poets, as the first of the delicate sense, and among the people who felt most of these words, stood by them. With its various colors and shapes, it has visible and hidden connotations, but the poet invokes it out of necessity for him to come with it, there are meanings and symbols that can only be reached through these words And the poet M.Haider al-Hilli is one of the poets who drew from the words of nature, and those words were mixed with his poetic purposes, but they emerged expressive and sincere in his lamentation of (Al-Bayt), those poems that were considered one of the greatest and most honorable what the poet presented, as they won the admiration of all people and became more like a purpose Independent from the rest of the objects, so the poet presented in its light the truest and most accurate feelings, until it seemed to be a painting embroidered with pain and pains at times, and sublime and elevation at other times, in addition to that, it shed light on an event that has a painful effect on the souls of Muslims. , In this research, we will present the indications that the words of nature came to, and the extent of the poet’s success in matching the context with those words, as well as the effect of those words on the recipient’s soul.
Keywords: Haider Al-Helee- words of nature-Lament.